American Values as Reflected in The Portrait of A Lady by Henry James - Andi Febriana Tamrin; Elfiranti Elfiranti (Interference: Journal of Language, Literature, and Linguistics, 2022)
Abstract. This research aimed to discover the elements of American values characters in The Portrait of A Lady novel by Henry James based theory of (L. Robert Kohls, 1984). The method of this research was descriptive qualitative. The main source of the data of this research was the novel The Portrait of A Lady, which published on 2001, consists of 55 chapters, and 687 pages. Meanwhile, the instrument of this research was note taking. The technique of data analysis of this research was linked to the story, concept, and method. Based this research, researcher found some parts of values in the novel based on Kohls’s theory. The results found, there are four American values characters in the novel, namely personal control over the environment, change, independence, future orientation and optimism. It was concluded that some of the previous American values are depicted in the novel The Portrait of A Lady.Keywords: American Values, Structuralism, The    Portrait of A Ldy, Isabel Archer, Character